Aligning metrics with meaning: considerations for measurement selection in disability evaluation - Marfeo, Elizabeth; Rasch, Elizabeth K.; Coale, Kathleen; Porcino, Julia; Chan, Leighton (Frontiers in Rehabilitation Sciences, 2025)
This article explores the role of patient-reported outcome measures (PROMs) in disability evaluation, a measurement domain traditionally dominated by clinical performance-based assessments. While performance tests are valued for their perceived objectivity, PROMs have gained prominence in research for their efficiency, patient-centered orientation, and capacity to capture subjective experiences relevant to functional decline related to potentially disabling conditions. The manuscript underscores the importance of aligning measurement tools with the specific purpose of evaluation—whether clinical, policy-driven, or programmatic. Using the Work Disability Functional Assessment Battery (WD-FAB) as an illustrative case, it compares the strengths and limitations of PROMs and performance-based tools in evaluating mental and physical function in the context of disability assessment. PROMs such as the WD-FAB can systematically and efficiently generate scores that represent function across multiple domains of function (e.g., mood and emotion, mobility, cognition) and are particularly well-suited for detecting change over time in large-scale applications. In contrast, performance-based assessments, while useful in certain clinical scenarios, are often resource-intensive and may not accurately reflect real-world functioning. The paper argues that although PROMs should not replace performance measures entirely, they represent a valuable and often preferable alternative or complement in many disability evaluation contexts. Ultimately, the choice of assessment tool should consider the intended use, resource constraints, and the need for comprehensive, patient-centered data.